Does Entrepreneur Innovativeness Moderate The Relationship Between Strategic Orientation And Financial Inclusion? - Nguli, Judith Ndinda; Odunga, Robert Mukoswa (SEISENSE Journal of Management, 2019)
Purpose- Although previous papers have attempted to explore the determinants of financial inclusion, few studies have interrogated the role of innovativeness in financial addition. This study examines the moderating role of entrepreneur innovativeness on the relationship between strategic orientation and financial inclusion Design/Methodology - We used two indicators to measure financial inclusion; digital financial inclusion scale and traditional financial inclusion scale. Three proxies were used to measure strategic orientation; learning orientation, market orientation, and technology orientation. Survey data obtained from 634 women entrepreneurs was used, and the hypothesis was tested using moderated regression analysis. Findings - The empirical results supported the hypothesis that innovative entrepreneur moderates the relationship between strategic orientation and financial inclusion. In particular, the results indicated that at higher levels of entrepreneur innovativeness, learning orientation has a stronger effect on financial inclusion. Similarly, the results also indicated that at high levels of entrepreneur innovativeness, technology orientation affects financial inclusion. In contrast with the other findings showing a positive moderating effect, at higher levels of entrepreneur innovativeness, the impact of market orientation on financial inclusion is low. Practical Implications - The findings are useful to the government and practitioners for designing policies and training programs geared to increasing the level of financial inclusion among women Small and Medium Enterprises.